Regional monetary cooperation in Latin America - José Antonio Ocampo; Daniel Titelman (Asian Development Bank Institute (ADBI), 2012)
Latin American has the longest history of regional integration efforts in the developing world. This paper analyzes the experience of regional monetary cooperation in Latin America over the past three decades. This experience has been overall successful but also uneven, both in terms of country coverage and services provided. Although strictly not a form of monetary cooperation, development financing does play a useful complementary role by proving counter-cyclical or at least stable financing during crises, when private financing for developing countries dries up.
Keywords: O23; O54; 330; regional monetary cooperation; latin america; regional integration; development financing; Entwicklungsfinanzierung; Entwicklungshilfe; Entwicklungsländer; Lateinamerika